Rightsizing as a Strategic Management Tool in Nigeria’s Public Sector - Gabriel, Oriloye; Eyitayo, Adewumi; Ayodele, Nwaodike Chibuzor (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Public sectorâ€™s rightsizing entails the unbundling of the institutional architecture of states administrative apparatus which include restructuring exercise for effectiveness and efficiency. The Nigerian public sectorâ€™s performance has been characterized with low productivity in its statutory responsibilities despite the huge budget allocation. In order to reposition the public sector in Nigeria, Goodluck Jonathan administration initiated a reform to restructure the public service to have value for money, increase efficiency, identify and set targets as well as monitor performance. The study adopted survey research design. The population of the study was 541, drawn from the human resources personnel department of selected public parastatals.  The population figure was drawn from the following public agencies: Economic and Financial Crimes Commission (EFCC) 108, Independent Corrupt Practices and other related offences Commission (ICPC) 96, Nigeria Civil Aviation Authority (NCAA) 288 and Nigeria Metrological Agency (NIMET) 49. Yamane formula was used to calculate the sample size of 230. Instrument of data collection was questionnaire. Data analysis was in descriptive statistics with the use of mean, standard deviation, and frequencies. Findings revealed that rightsizing was not practiced in Nigeria public sector despite its relevance to human capital planning. It therefore recommended a strong practice of rightsizing in the Public Sector to facilitate much more result in the area effective human capital planning, efficiency, regular personnel audit, the maintenance of accurate personnel records, effective plan for immediate and future human capital need. It will expose irregularities such as ghost workers, redundant staff and workers with fake certificates. Keywords : Rightsizing, Management, Tool, Strategic, Public Sector